High velocity blue-shifted FeII absorption in the dwarf star-forming galaxy PHL293B: Evidence for a wind driven supershell? - Terlevich, Roberto (2014)
A2228-00 and SDSS J223036.79-000636.9 are presented in this paper. We find broad (FWHM = 1000km/s) and very broad (FWZI = 4000km/s) components in the Balmer lines, narrow absorption components in the Balmer series blueshifted by 800km/s, previously undetected FeII multiplet (42) absorptions also blueshifted by 800km/s, IR CaII triplet stellar absorptions consistent with [Fe/H] < −2.0 and no broad components or blushifted absorptions in the HeI lines. Based on historical records, we found no optical variability at the 5 σ level of 0.02 mag between 2005 and 2013 and no optical variability at the level of 0.1mag for the past 24 years. The lack of variability rules out transient phenomena like luminous blue variables or SN IIn as the origin of the blue shifted absorptions of HI and FeII. The evidence points to either a young and dense expanding supershell or a stationary cooling wind, in both cases driven by the young cluster wind.